Activating Azides and Alkynes for the Click Reaction with [Cu(aNHC)2I] or [Cu(aNHC)2]+ (aNHC = Triazole‐Derived Abnormal Carbenes): Structural Characterization and Catalytic Properties. Issue 22 (22nd May 2013) - Hohloch, Stephan; Scheiffele, Damaris; Sarkar, Biprajit
Abstract: Neutral, iodido‐containing copper(I) complexes [Cu( a NHC)2 I] a NHC = 1‐benzyl‐3‐methyl‐4‐phenyl‐1, 2, 3‐triazol‐5‐ylidene (for6 ) and 3‐methyl‐1‐[2‐(methylthio)phenyl]‐4‐phenyl‐1, 2, 3‐triazol‐5‐ylidene (for7 ) and cationic, halide‐free copper(I) complexes [Cu( a NHC)2 ](BF4 ) a NHC = 1‐benzyl‐3‐methyl‐4‐phenyl‐1, 2, 3‐triazol‐5‐ylidene (for8 ), 3‐methyl‐1, 4‐diphenyl‐1, 2, 3‐triazol‐5‐ylidene (for9 ), 3‐methyl‐1‐[2‐(methylthio)phenyl]‐4‐phenyl‐1, 2, 3‐triazol‐5‐ylidene (for10 ), and 1‐mesityl‐3‐methyl‐4‐phenyl‐1, 2, 3‐triazol‐5‐ylidene (for11 ), both containing two monodentate abnormal‐carbene ligands ( a NHC), were synthesized from [Cu(CH3 CN)4 ](BF4 ) and the corresponding triazolium salts. It was possible to selectively synthesize both kinds of complexes by simply variing the counter‐anion of the triazolium salts and keeping the metal precursor the same. All complexes were characterized by elemental analysis and spectroscopic methods.6 and11 were studied with single‐crystal X‐ray diffraction analyses. In6, the copper(I) center is tricoordinated, and its geometry is in between trigonal planar and T‐shaped. In halide‐free11, the copper(I) center is linearly coordinated by two abnormal‐carbene ligands. All complexes were tested as catalysts in the Huisgen [3+2] cycloaddition reaction between azides and alkynes, and they showed excellent efficiencies under neat conditions. A comparison between the efficiencies of the halide‐containing complexes6 and7 and the halide‐free cases8 –11, shows that the halide‐free Cu– a NHC complexes are significantly more efficient than their halide‐containing counterparts. The best catalyst was used for a substrate screening by utilizing a variety of azides and a couple of alkynes. The efficiency of the catalyst was maintained with loadings as low as 0.005 mol‐%. Mechanistic studies were carried out as well. Abstract : Cationic copper(I) complexes containing two triazolylidene carbenes of the abnormal type are shown to be excellent catalysts for the [3+2] cycloaddition reaction between azides and alkynes. A range of azides and a couple of alkynes are activated by these copper(I) complexes towards the catalytic formation of the corresponding substituted 1, 2, 3‐triazoles.